Pendampingan Tata Kelola Administrasi Kelurahan Kalisegoro Kecamatan Gunungpati Kota Semarang - Bambang Guritno; Edy Priyanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Village administrative governance is very important in the administration of village governance. Because the village government will be able to carry out its duties properly and correctly if it is supported by good village administrative management. This research was conducted to explain the administrative governance of the Kalisegoro village, Ngijo Gunung Pati sub-district, Semarang. By using a qualitative design, it was found that transparency, accountability, responsibility, independence, as well as equality and fairness are aspects that need to be carried out in realizing administrative governance of the Kalisegoro sub-district, Ngijo Gunung Pati sub-district, Semarang.